Modelling biopharmaceutical manufacture: Design and implementation of SimBiopharma - Farid, Suzanne S.; Washbrook, John; Titchener-Hooker, Nigel J. (Computers & chemical engineering, 2007)
This paper presents the implementation of a conceptual framework, for modelling a biopharmaceutical manufacturing plant, into a prototype decision-support tool, SimBiopharma. The tool's scope covers the ability to evaluate manufacturing alternatives in terms of cost, time, yield, resource utilisation and risk. Incorporating uncertainty means that investment appraisal can be based on both the expected outputs and the likelihood of achieving them. A hierarchical approach to represent the key activities in a manufacturing process is introduced. Emphasis is placed on how a closer integration of bioprocess and business process modelling can be achieved by capturing common information in an object-oriented environment, G2 (Gensym Corporation, Cambridge, MA). The key features of SimBiopharma are highlighted; these include interactive graphics, task-oriented representation and dynamic simulation which create a much more flexible environment for modelling processes. Examples of typical outputs generated by SimBiopharma, when addressing the impact of manufacturing options on strategic operational and financial indicators, are given.